Epidemiological Aspect of Dog Bite and Response of The Dog Bite Victims Attending Vaccination Centre of Sadar Hospital, Sirajganj - Alam, Ahmed Nawsher; Siddiqua, Mahmuda; Siddiqua, Asma; Akther, Nasreen; Sarker, Moushumi; Biswas, Sailendra Nath; Bose, Chandra Shekhor (KYAMC Journal, 2019)
Background: Rabies is a public health problem in Bangladesh, with poorer people and children being mainly affected. Objectives: The aim of this study was to investigate the behaviours of dog bite victims following a bite and to assess the knowledge and attitude about rabies among dog bite victims. Materials and Methods: A crosssectional type of descriptive study was designed where individual people who came to the vaccination centre from the month of April 2015 to July 2015 for post-exposure prophylaxis were considered. They were interviewed and followed during subsequent visits until they had received their final dose of vaccination. Result: Among the victims, males 60.9% were more common than females 39.1% and most of them were children aged below 20 years 51 %, mostly from rural areas 69.3%, had very little primary 46.1% or no education 24.7%. Victims were bitten mostly at their legs 89.3%. In response to question regarding what happens following dog bite, 49% couldn't say anything, and 46% mentioned hydrophobia. Most of them (87%) know that rabies can be transmitted from dogs to humans; 68.4% had no idea that rabies can be prevented in dogs. Though 82.3% bite victims didn't know that rabies in humans can be prevented before a dog bite, 77.7% knew that rabies can be prevented after a dog bite. Use of soap and water was found lowest 13.1% among those who had education upto primary level and highest 53.9% in graduates. Conclusion: This study showed that most victims didn't take any washing measures before visiting to hospital which is one of the most important measures recommended by WHO and it was found mostly who had low education level. It also observed that knowledge gap about rabies among the dog bite victims decreased with increased education level. KYAMC Journal Vol. 9, No.-4, January 2019, Page 148-152